CENTRAL HIGHLANDS’ TALES AND SOUTHEAST ASIAN TALES - SEVERAL COMMON MOTIFS - Lê Hồng Phong (Tạp chí Khoa học Đại học Đà Lạt)
Central Highlands’ tales and Southeast Asian tales are similar and dissimilar in terms of genres, characters, content, and literature and cultural values. This article presents several similarities and a few dissimilar between the tales of the Central Highlands and those in the region of ASEAN in terms of motifs.